DEVELOPMENT FAILURE IN LOW-INCOME COUNTRIES: THE COMPLEXITY OF MULTIDIMENSIONAL POVERTY IN MOZAMBIQUE - Ariningtyas, Sukma Ayu Putri (Department of International Relations Universitas Satya Negara Indonesia, 2025)
This research seeks to analyze how multidimensional poverty, rooted in multisectoral problems, contributes to development failure in Mozambique. This study elucidates that multidimensional poverty in Mozambique is entrenched in political and security crises, as well as the instability of community socio-economic conditions. These issues arise from historical, socio-economic, and political dynamics, alongside a crisis of democracy, corruption, and debt. The study examines these challenges through the lens of the Multidimensional Poverty Index (MPI) to accurately explain the poverty conditions in Mozambique. Employing qualitative analysis and a comprehensive literature review, this research facilitates an in-depth understanding of the relationship between development failure and multidimensional poverty in Mozambique. The findings reveal that prolonged poverty in Mozambique is influenced by a multitude of factors, including weak enforcement of human rights, corruption, conflict and security crisis, income inequality, inadequate public infrastructure, and other critical challenges. This research contributes to enriching literature about multidimensional poverty, highlighting the correlation between this kind of poverty in poor countries and their national development failures.